Fertility desires and utilization of an integrated HIV care and family planning services among young women living with HIV in semi-rural Uganda: A cross sectional study - Edward Kumakech; Deo Benyumiza; Marvin Musinguzi; Wilfred Inzama; Doryn Ebong; James Okello; Lydia Kabiri; Jasper Watson Ogwal-Okeng (PLoS ONE, 2026)
Background Little is known about the fertility desires among young women living with HIV (YWLHIV) in sub-Saharan African (SSA) settings and its association with their utilization of an integrated HIV care and family planning (FP) services. This study assessed the fertility desires and the utilization of an integrated HIV care and FP services among YWLHIV in Northern Uganda, where limited data exist to inform the integration of contraception, safer conception and prevention of mother to child (PMTCT) of HIV services. Methods In a cross-sectional study design, we collected data from YWLHIV attending antiretroviral therapy (ART) clinics in northern Uganda between November 2022 and April 2023. Using an interviewer-administered questionnaire, participants were asked about their fertility desires and the potential associated factors which included the socio-demographic, HIV, ART, sexual and reproductive health (SRH) and access to the community-based SRH resources. They were also asked whether they ever received FP services from the ART clinic facilities where they usually obtain their HIV care. Descriptive statistics for fertility desires and level of utilization of the integrated HIV and FP services were performed. More so, Chi-square test, Fisher’s Exact test, bivariate and multivariable Poisson regression analyses for the associations between the predictor variables and the fertility desires were performed. The 5% significance level and 95% confidence intervals were considered for the measures of fertility desires and the associations. Results We recruited 423 YWLHIV with a median age of 22 (IQR 20–24) years. The data revealed a high fertility desire (88.9%) among the YWLHIV. Single women exhibited 24% lower fertility desires than their married counterparts (p = 0.013). Women who did not know of the integrated FP services offered from the ART clinic facilities had 18% lower fertility desires than their counterparts who knew (p = 0.045). Conversely, women with a positive history of planned pregnancies showed 17% higher fertility desires than their counterparts with positive history of unintended pregnancies (p = 0.040). Similarly, current modern contraceptive users had 23% lower fertility desires than their counterparts who were non-current users (p = 0.003). The utilization of an integrated HIV care and FP services was significantly lower (30.1%) among the YWLHIV with fertility desires compared to 48.9% among those without fertility desires (X 2 5.991, df 1, p = 0.014). Conclusions The study found a high fertility desires but lower utilization of an integrated HIV care and FP services among the YWLHIV in a Ugandan setting. Whereas the factors responsible for the low utilization of an integrated HIV and FP services remains question for future research, being married, having knowledge and receiving modern contraceptive methods from the ART clinic facility, experiences of planned pregnancy and non-current use of modern contraceptives were associated with the higher odds of fertility desires among the YWLHIV. These findings highlight the need to address the low utilization of an integrated HIV care and FP services, marital expectations and modern contraceptive access within the HIV care for YWLHIV with fertility desires.